Safety Verification of SEITR Epidemic Model on Recombination HIV and Hepatitis B Virus using Taylor Model - Asmudik Asmudik; Dieky Adzkiya; Mardlijah Mardlijah; Hariyanto Hariyanto ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2021)
Human Immunodeficiency Virus (HIV) is an AIDS (Acquired Immuno Deficiency Syndrome) virus that attacks the immune system for which there is no cure. When the immune system has decreased, it is prone to diseases such as Hepatitis B disease. To reduce the error value of the number of subpopulations, we use an interval approximation. One of the simulation calculations that the number of variables initially intervals is Taylor model. Taylor's model can be used to verify that the number of people infected with HIV and Hepatitis B will not exceed the specified number of unsafe sets. To calculate the set of states that are reached by the system over a certain period of time, given the initial conditions and parameters. The initial condition is divided into three scenarios, an affordable set of states, safety verification can be done. As a result of the safety verification of the three scenarios provided there is no set of states that are not safe, so the results of all three scenarios are safe.